2017
DOI: 10.1086/691192
|View full text |Cite
|
Sign up to set email alerts
|

Mating System Evolution under Strong Pollen Limitation: Evidence of Disruptive Selection through Male and Female Fitness in Clarkia xantiana

Abstract: Selection on floral traits in hermaphroditic plants is determined by both male and female reproductive success. However, predictions regarding floral trait and mating system evolution are often based solely on female fitness. Selection via male fitness has the potential to affect the outcomes of floral evolution. In this study, we used paternity analysis to assess individual selfing rates and selection on floral traits via male and female fitness in an experimental population of Clarkia xantiana where pollen l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 84 publications
0
37
0
Order By: Relevance
“…Apart from the issue of life span, it is often most convenient to assess fitness through maternity, ignoring paternal fitness variation because of the difficulty of attributing offspring to particular sires. It is now, however, feasible to assign paternity with considerable confidence (e.g., Kulbaba and Worley 2012;Briscoe Runquist et al 2017). With such information, FTNS could be applied using estimates based on either maternal fitness or paternal fitness.…”
Section: Predicting Adaptationmentioning
confidence: 99%
“…Apart from the issue of life span, it is often most convenient to assess fitness through maternity, ignoring paternal fitness variation because of the difficulty of attributing offspring to particular sires. It is now, however, feasible to assign paternity with considerable confidence (e.g., Kulbaba and Worley 2012;Briscoe Runquist et al 2017). With such information, FTNS could be applied using estimates based on either maternal fitness or paternal fitness.…”
Section: Predicting Adaptationmentioning
confidence: 99%
“…Finally, reduced reliability of pollination is often associated with shifts in mating systems (rate of self-pollination), and will typically involve changes in traits that confer reproductive assurance, notably herkogamy and dichogamy (e.g. Moeller, 2006;Dart et al, 2012;Opedal et al, 2016Opedal et al, , 2017Briscoe Runquist et al, 2017). Therefore, a predictive understanding of plant adaptation to novel pollinator communities will also require knowledge of variation in evolvabilities among trait groups.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of selection on self-pollination have estimated current levels of inbreeding depression, pollen discounting, and seed discounting (Busch & Delph, 2012;Husband & Schemske, 1996;Layman, Fernando, Herlihy, & Busch, 2017;Rausher, Augustine, & Vanderkooi, 1993), and whether selfing is favored in conditions of pollen or pollinator limitation (Briscoe Runquist, Geber, Pickett-Leonard, & Moeller, 2017;Fishman & Willis, 2008;Gervasi & Schiestl, 2017;Moeller & Geber, 2005;Roels & Kelly, 2011;Strandh et al, 2017;Toräng et al, 2017). However, we know of fewer direct demonstrations of overall selection favoring selfing, although a recent study in Leavenworthia found molecular signatures consistent with positive selection on the S-locus (Herman & Schoen, 2016).…”
mentioning
confidence: 99%